Strengthening Communicable Disease Response: Developing Quarantine And Isolation Policies And Training For Disease Investigations In Jackson County - Willis, Reese (My University, 2024)
This Integrative Learning Experience (ILE) report details my Applied Practice Experience (APE) at Jackson County Public Health (JCPH) in Missouri, focusing on strengthening the county’s response to communicable disease outbreaks. The primary objectives were to assist in developing a comprehensive Quarantine and Isolation (Q/I) policy and to create a Professional Development Day (PDD) training module on communicable disease investigation for public health staff. The development of the Quarantine and Isolation policy involved creating essential materials, such as detailed flowcharts for managing vaccine-preventable and non-vaccine-preventable diseases, a tracking sheet for monitoring individuals in quarantine and isolation, and a reference report outlining legal frameworks and support services. Jackson County previously lacked a formal system for managing quarantine and isolation, and this policy is intended to transition into a county ordinance. By providing structured procedures and data tracking capabilities, the policy equips JCPH with an organized and legally sound framework to manage future outbreaks more effectively. The Professional Development Day training module was designed to enhance staff capacity by educating over 60 JCPH employees on key public health topics, including epidemiology, disease surveillance, and contact tracing. The training included a comprehensive lecture and an interactive case investigation activity, where staff simulated investigating outbreaks of diseases like Salmonella, Pertussis, and Legionella. This hands-on approach aims to equip the entire staff with essential skills for managing outbreaks, improving coordination and efficiency. By applying Master of Public Health (MPH) foundational competencies, such as epidemiological methods, communication strategies, and systems thinking tools like process mapping, this project significantly strengthened JCPH’s preparedness for future outbreaks. These initiatives contribute to a more robust public health infrastructure in Jackson County, ensuring effective response capabilities for communicable disease control.
Keywords: Communicable disease; Quarantine; Isolation; Outbreak response; Public health training; Systems thinking